Analysis of Teacher Problems in Implementing Class 3 Thematic Learning Implementation Plans at Sukahati State Elementary School - Risfa Khoerunisa Harliani; Endah Parawangsa; Deti Rostika (CV. Rayyan Dwi Bharata, 2023)
Education is an attempt to maintain and develop the human personality mentally and physically. As according to Ki Hajar Dewantara. Thematic learning is an approach to learning that emphasizes integration between various disciplines or subjects in one particular theme or topic. In thematic learning, the topics chosen usually have strong relevance to the daily lives or needs of students, so that students can see the relationship between the knowledge they are learning and the wider context. At SDN Sukahati, there are 3 problems in implementing thematic lesson plans.